Effectiveness of nurse-led clinics in the early discharge period after percutaneous coronary intervention: A systematic review. Issue 5 (September 2021) - Corones-Watkins, Katina; Cooke, Marie; Theobald, Karen; White, Katherine; Thompson, David R.; Ski, Chantal F.; King-Shier, Kathryn; Conway, Aaron; Ramis, Mary-Anne
Abstract: Background: Readmission after percutaneous coronary intervention is common in the early postdischarge period, often linked to limited opportunity for education and preparation for self-care. Attending a nurse-led clinic within 30 d after discharge has the potential to enhance health outcomes. Objective: The aim of the study was to synthesise the available literature on the effectiveness of nurse-led clinics, during early discharge (up to 30 d), for patients who have undergone percutaneous coronary intervention. Review method used: A systematic review of randomised and quasi-randomised controlled trials was undertaken. Data sources: The databases included PubMed, OVID, CINAHL, EMBASE, the Cochrane Library, SCOPUS, and ProQuest. Review methods: Databases were searched up to November 2018. Two independent reviewers assessed studies using the Cochrane risk-of-bias tool. Results: Of 2970 articles screened, only four studies, representing 244 participants, met the review inclusion criteria. Three of these studies had low to moderate risk of bias, with the other study unclear. Interventions comprised physical assessments and individualised education. Reported outcomes included quality of life, medication adherence, cardiac rehabilitation attendance, and psychological symptoms. Statistical pooling was not feasible owing to heterogeneity across interventions, outcome measures, and study reporting. Small improvements in quality of life and some self-management behaviours were reported, but these changes were not sustained over time. Conclusions: This review has identified an important gap in the research examining the effectiveness of early postdischarge nurse-led support after percutaneous coronary intervention on outcomes for patients and health services. More robust research with sufficiently powered sample sizes and clearly defined interventions, comparison groups, and outcomes is recommended to determine effectiveness of nurse-led clinics in the early discharge period.